Designed Questionnaire to Evaluate the Performance of Hospital Emergency - Ali Akbarisari; Farhad Habibi; Bahman Khosravi; Pejman Hamouzadeh; Mani Yousefvand (Tehran University of Medical Sciences, 2020)
Background: Performance appraisal and quality evaluation of the services provided will achieve the organizational goals and improve the level of staff capability. In order to evaluate accurately and efficiently, we need to use standard indices, to compare the quality and quantity of work with standards, to know the current conditions and to solve its problems  Methods: This study is an applied study. This was done through a combined method of reviewing the texts and consensus of experts. Initially, the literature review and emergency evaluation indices were extracted, then the duplicate indices were removed and similar indices were merged, then weighted experts and questionnaires were compiled with the indices. Content validity, Cronbachchr('39')s alpha coefficient and test-retest were used to assess the validity, internal consistency and reproducibility of the questionnaire, respectively. Data were analyzed using Excel and SPSS 20 software.  Finding: Final questionnaire with 105 questions in 8 areas including management and leadership (15); human resources (22); physical space and facilities (18); medicine and medical equipment (6); guidelines and policies (17); patient-centered (10); documentation of patient records (5); quality and time indices in the emergency department (12). The results showed that the final questionnaire was reliable (0.89) and repeatable (ICC = 0.98). Conclusion: The Hospital Emergency Performance Assessment Questionnaire is a valid and reliable instrument and can be used to evaluate the performance of hospital emergency services.